Factors That Influence Water Demand in Special Region Yogyakarta - Auladina Rizqina; Deky Aji Suseno (Economics Development Analysis Journal, 2020)
The demand for water in Special Region Yogyakarta, which is increasing every year, is not matched by the quality and effectiveness of water production. The distribution of PDAM water is uneven in every region in the Special Province of Yogyakarta. The purpose of this study is to determine the effect of water prices, the number of hotels, the number of industries, and the GRDP per capita of the population, also, in order to determine the effect of employee retribution and operational costs of the PDAM on PDAM water prices. The study uses secondary data analysis technique used is descriptive statistical analysis and SEM structural modeling analysis. The results showed that the number of employees had a significant positive effect on remuneration for PDAM employees. Reply to PDAM employee services and PDAM operational costs affect water prices. At the same time, the price of PDAM water and GDRP per capita of the population has a significant positive effect on PDAM water demand. The number of hotels and industries that subscribe to water in PDAMs has a significant negative effect on water demand.